Lisbon heat island statistical study (2004-2012) - Alcoforado,Maria João (2014)
With the aim of implementing climatic guidelines for planning purposes, the urban climate of each particular city must be assessed, particularly the frequency of unwanted climatic features, such as the Urban Heat island (UHI). As the Lisbon “Mesoscale urban meteorological network” (CEG-IGOT-ULisboa) has been running since 2004, it is now possible to present statistical results about the UHI. It was calculated on an hourly basis as the difference between one of the “central” measurement points (Restauradores or Saldanha) and one of the eccentric points of the network (Carnide or Monsanto). UHI is more intense in summer (maximum hourly averages up to 6.3ºC) than in winter (up to 3.8ºC), and more intense during the night than during the day. in Lisbon, its causes are not only due to the modification of energy balance in urban areas, but also to the shelter effect from the prevailing and cold/cool north winds, due to the topography and the buildings.